Theoretical Knowledge of Subject of Home Management with Its Practical application In Home Management Residence. - Maryam, Madiha; Siddiqui, Nabiha; Nargis, Sumaira (Nurture, 2016)
This study has tried to explore undergraduate students’ knowledge and skills related competencies in various areas of home management.. Data was collected from 100 students of Rana Liaquat Ali khan College of Home Economics currently enrolled in B.S program and who had completed two-weeks live-in training program in Home Management. A self-administered questionnaire was used that had prepared to assess knowledge and skills from the domains of “Management process”, “Decision-making”, “motivation for management”, “resources”, and “work simplification”. Competence in knowledge was assessed by correctness of answers to theoretical questions and competence in skill in applying the knowledge was assessed by use of that knowledge during the live-in training program (Residence program). Internal consistency of items was analyzed through Cronbach’s alpha. Overall students scored better in knowledge as compared to skills in application. . However, students have shown application of theoretical knowledge of decision-making, values, goals and standards